Utility of mangled extremity severity score in severely injured lower limbs - Toya Raj Bhatta (Society of Surgeons of Nepal, 2017)
Introduction: Massive lower extremity trauma,in particular open tibial fractures with associated vascular injuries, present an immediate and complex decision-making challenge between a limb salvage attempt and primary amputation. Medical and surgical advances of the past two decades have improved the ability to reconstruct severely injured limb. Limbs that once would have been amputated are now routinely managed with complex reconstruction protocol. Mangled extremity severity score is one of the scoring systems to predict the fate of limbs after severe limb injuries.